Reconsidering the ecological effect of seed endophytes in building plant microbial environments: lessons from a Chinese medicinal plant Panax notoginseng - Wen, Yun; Yang, Wei-Xi; Li, Yi-Qian; Lu, Chun-Xi; Hu, Hong-Yan; Guo, Li-Rong; Huang, Shuang-Ye; Pan, Xiao-Xia; Zhu, Shu-Sheng; Yang, Ming-Zhi (Environmental microbiome, 2025)
Seed endophytes (SEs) are of particular interest in the fields of plant science, microbiology and agronomy due to their unique spatial and functional relationship with the host plant. SEs formed originally in mother plants, represent the majority of vertically transmitted endophytes (VTEs) in plants, and the inheritance of SEs by plants is a strategy to cope with environmental challenges. However, despite the growing interest in seed endophytes (SEs), our understanding of the host effects of SEs and their transmission remains limited. Here, seeds of a Chinese medicinal plant, pseudoginseng (Pg), were germinated and cultivated separately in autoclaved and natural guest soils under aseptic conditions, and the vertically transferred SEs (sVTEs) in the progeny plant endophytic and rhizospheric soil microbiomes were examined using an amplicon-based approach. We first categorized the detected Pg SE amplicon sequence variants (ASVs) into sVTEs and other SEs (nVTEs) based on the ASV overlap analyses, and an apparent taxa bias in sVTE was observed for both bacteria and fungi. Bacterial sVTEs are characteristically motile, biofilm forming and stress tolerant. The presence of soil-dwelling microbes did not prevent progeny plants from inheriting levels of sVTEs from seeds, but involved in shaping the composition of the acquired sVTEs. Most importantly, an aseptic cultivation experiment showed that the SEs alone were able to establish a high diversity of plant-associated microbiota (PAM) in progeny plants via vertical transmission; and sVTEs were acted as a core microbiota that dominated the assembly of the progeny PAM (with the relative abundances ranged from 21 to 79%) in both the natural and sterilized soil cultivation experiments. However, the impact of sVTEs on PAM assembly may be more significant than is currently recognized, given that proportions of SEs and sVTEs in plant seeds remain undetected due to technological limitations and small sample sizes. The work has advanced our knowledge of the nature of sVTEs and the ecological effects of SEs on host plants.